Asymptotic behaviour of the solutions of a class of (k+1)-order rational difference equations - Georgiev, Svetlin G. (Sarajevo Journal of Mathematics, 2022)
In this paper we investigate the solutions of a class of (k+1)-order rational difference equations. We give conditions for the parameters ensuring that the considered equation has a unique positive equilibrium point that is locally asymptotically stable and every positive solution of the considered equation is bounded and increasing and converges to the unique positive equilibrium point.